Rethinking regional performance: examining the role of economic growth and industrial clusters in the objective well-being of European regions - Nils Grashof (Review of Regional Research, 2025)
While promoting the well-being of people is the ultimate goal of all EU social and economic policies, research in this area has been mainly limited to income-based measures of well-being, such as GDP per capita, especially at the regional level. Therefore, this study aims to go beyond income-based measures and examine the spatial distribution and drivers of objective well-being in European regions. To achieve this, a unique panel dataset is created by integrating regional data on objective well-being (based on the EU-Social Progress Index), economic growth, industrial clusters and knowledge structure, covering 165 NUTS-2 regions from 11 EU countries (between 2011 and 2018). Based on dynamic panel regressions using a system generalized method of moments (GMM) approach, it is shown that the economic growth promotes the objective well-being in regions. Evidence is also found that the industrial structure within regions is an additional driver. Regions with a diverse industrial cluster portfolio are more likely to have high objective well-being. However, this influence is negatively moderated by the strength of the industrial clusters, which possibly refers to size-related negative externalities. Besides the economic effects, industrial cluster structures can therefore also influence the objective well-being in regions. To promote regional well-being, regional policies should support a diverse industrial cluster portfolio rather than a regional cluster structure that is overly specialized in relatively few large industries. – – Obwohl die Förderung des Wohlstands der Menschen das oberste Ziel aller sozial- und wirtschaftspolitischen Maßnahmen der EU ist, beschränkte sich die Forschung in diesem Bereich bisher hauptsächlich auf einkommensbasierte Maße des Wohlstands, wie das BIP pro Kopf, insbesondere auf regionaler Ebene. Daher zielt diese Studie darauf ab, über einkommensbasierte Messgrößen hinauszugehen und die räumliche Verteilung und die Triebkräfte des objektiven Wohlstands in europäischen Regionen zu untersuchen. Hierzu wird ein Paneldatensatz erstellt, der regionale Daten zum objektiven Wohlstand (basierend auf dem EU-Index für sozialen Fortschritt), zum Wirtschaftswachstum, zu Industrieclustern und zur Wissensstruktur enthält und 165 NUTS-2-Regionen aus 11 EU-Ländern (zwischen 2011 und 2018) abdeckt. Auf der Grundlage dynamischer Panel-Regressionen unter Verwendung einer verallgemeinerten Momentenmethode (GMM) wird gezeigt, dass das Wirtschaftswachstum den objektiven Wohlstand in Regionen fördert. Es wird auch nachgewiesen, dass die Industriestruktur innerhalb der Regionen ein zusätzlicher Einflussfaktor ist. Regionen mit einem breit gefächerten Portfolio von Industrieclustern haben eine höhere Wahrscheinlichkeit für ein hohes objektives Wohlergehen. Dieser Einfluss wird jedoch durch die Stärke der Industriecluster abgeschwächt, was möglicherweise auf größenbedingte negative Externalitäten zurückzuführen ist. Neben den wirtschaftlichen Effekten können industrielle Clusterstrukturen also auch das objektive Wohlergehen in Regionen beeinflussen. Um das regionale Wohlergehen zu fördern, sollte die Regionalpolitik ein vielfältiges Portfolio von Industrieclustern unterstützen und nicht eine regionale Clusterstruktur, die übermäßig auf relativ wenige große Industrien spezialisiert ist.
Keywords: 910; Well-being; Objective well-being; GDP; Clusters; Agglomeration; European regions